Gender identity and the management of the transgender patient: a guide for non-specialists - Joseph, Albert (J R Soc Med, 2017)
In this review, we introduce the topic of transgender medicine, aimed at the non-specialist clinician working in the UK. Appropriate terminology is provided alongside practical advice on how to appropriately care for transgender people. We offer a brief theoretical discussion on transgenderism and consider how it relates to broader understandings of both gender and disease. In respect to epidemiology, while it is difficult to assess the exact size of the transgender population in the UK, population surveys suggest a prevalence of between 0.2 and 0.6% in adults, with rates of referrals to gender identity clinics in the UK increasing yearly. We outline the legal framework that protects the rights of transgender people, showing that is not legal for physicians to deny transgender people access to services based on their personal beliefs. Being transgender is often, although not always, associated with gender dysphoria, a potentially disabling condition in which the discordance between a person’s natal sex (that assigned to them at birth) and gender identity results in distress, with high associated rates of self-harm, suicidality and functional impairment. We show that gender reassignment can be a safe and effective treatment for gender dysphoria with counselling, exogenous hormones and surgery being the mainstay of treatment. The role of the general practitioner in the management of transgender patients is discussed and we consider whether hormone therapy should be initiated in primary care in the absence of specialist advice, as is suggested by recent General Medical Council guidance.